Q is for duck : an alphabet guessing game - Elting, Mary, 1909-; Folsom, Michael (New York : Houghton Mifflin/Clarion Books, 1980)
While learning some facts about animals, the reader is challenged to guess why A is for zoo, B is for dog, and C is for hen.
Keywords: Alphabet; Animals